Ka raṅʻ Praññʻ nayʻ, Bhāʺ ʼaṃ mruiʻ mettā ññvanʻʺ phoʻ Rvhe Yañʻ Myhoʻ Cetī toʻ nhaṅʻʹ phāʺ nagāʺ samuiṅʻʺ - Dīpa, Moṅʻ (Dīpa Cuiʺ Cā pe, 1994)
History of Rvhe Yañʻ Myhoʻ Cetī, Buddhist temple in Pa-an, Burma.